Research Methods for the Behavioral Sciences, 6th Edition - Frederick J Gravetter; Lori-Ann B. Forzano (Cengage Learning, 2018)
In RESEARCH METHODS FOR THE BEHAVIORAL SCIENCES, 6th Edition, Fredrick J Gravetter and Lori-Ann B. Forzano help students see how interesting and exciting experimental and nonexperimental research can be. The text leads students through the research process from start to finish, including tips and strategies for generating research ideas and hypotheses, selecting measures and participants, and designing research. This step-by-step approach emphasizes the decisions researchers must make at each stage of the process. The authors avoid a ""cookbook"" presentation of just the facts by linking terminology with applied concepts; their ""lecture in a book"" style emphasizes clear explanations of topics. Research examples present topics of particular interest to students, and content throughout the book reflects current APA guidelines. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.